2017
DOI: 10.11604/pamj.supp.2017.28.1.9477
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of cholera in western Kenya, 2015: a case control study

Abstract: Introductionin February 2015, an outbreak of acute watery diarrhea was reported in two sub counties in western Kenya. Vibrio cholerae 01 serotype Ogawa was isolated from 26 cases and from water samples collected from a river mainly used by residents of the two sub-counties for domestic purposes. We carried out an investigation to determine factors associated with the outbreak.Methodswe conducted a frequency matched case control study in the community. We defined cases as episodes of watery diarrhea (at least t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…However, most AWD outbreaks in Somalia have been attributed to Vibrio cholerae O1 Inaba confirming the clinical case definitions are valid for cholera surveillance (6). Despite these limitations, the study found a high AWD burden in Burhakaba IDP camps associated with poor WASH conditions and food insecurity, reflecting common challenges across Somalia (5,10).…”
Section: Discussionmentioning
confidence: 76%
“…However, most AWD outbreaks in Somalia have been attributed to Vibrio cholerae O1 Inaba confirming the clinical case definitions are valid for cholera surveillance (6). Despite these limitations, the study found a high AWD burden in Burhakaba IDP camps associated with poor WASH conditions and food insecurity, reflecting common challenges across Somalia (5,10).…”
Section: Discussionmentioning
confidence: 76%
“…In 2015, following an outbreak of cholera in Western Kenya, V. cholerae was isolated from river Riana in Migori. The same serotype of V. cholerae confirmed to be the source of the outbreak was also isolated from a patients' rectal swab 29 . The river was the source of water used for domestic purposes by the Migori people.…”
Section: Discussionmentioning
confidence: 79%
“…The river was the source of water used for domestic purposes by the Migori people. According to WHO 29 . Kenya experienced an outbreak of cholera that started in Tana river at the Coast and later reported in other counties: Garissa, Vihiga, Nairobi, Mombasa, Turkana, Kericho, Nakuru, Kiambu and Narok.…”
Section: Discussionmentioning
confidence: 99%
“…8 Bwire et al, in their study observed that Vibrio cholerae O1 was responsible for all outbreaks. 9 The two serotypes Inaba (8 out of 10 outbreaks) and Ogawa (responsible for 2 out of 10 outbreaks, in Namayingo and Wakiso districts) were isolated from stool samples.…”
Section: Resultsmentioning
confidence: 98%